Epigenetic Mechanisms in Cellular Reprogramming - Meissner, Alexander.; Meissner, Alexander.; Walter, Jörn.; Walter, Jörn. (Epigenetics and Human Health,, 2015)
The ability of a single genome to give rise to hundreds of functionally distinct cell type programs is in itself remarkable. Pioneering studies over the past few decades have demonstrated that this plasticity is retained throughout development, a phenomenon of epigenetic programming and reprogramming that remains one of the most fascinating areas of modern biology, with major relevance to human health and disease. This book presents the basic biology involved, including key mechanistic insights into this rapidly growing field.